Effects of visual field impairment on driving - Jan Andersson (218600) (2015)
Driving is a visually demanding task (Kotecha, Spratt and Viswanathan, 2008). Does individuals with visual deficits fulfill the “Fitness to drive” criteria? The developed simulator based method presented below was driven by the purpose to be able to discriminate between individuals with and without visual deficits. (Owsley, Wood, and McGwin, 2015). An advanced driving simulator was used to develop a simulated driving task, which also included a choice reaction test performed while driving on a rural road. Twenty-four drivers with various visual field impairments were compared to 55 drivers without visual defects. Two types of traffic signs positioned 5, 10, and 15 degrees (left, right) horizontally were used as stimuli. The test included both single and double stimuli. Drivers reacted by pressing buttons attached to the drivers fingers. It was found that the visually impaired drivers reacted 23% slower (1.46s vs. 1.19s) and had 14% less correct number of hits (74% vs. 84%) for single stimuli trials. Reaction time for double stimuli trials was 15% longer (1,68s vs. 1.46s) and hit rate was 27% less (69% vs. 88%). When the results from a secondary trial for drivers visual impairments were compared the normal sighted drivers’ first try the differences decreased but were still statistical significant. For single stimuli 17% slower, 5% less correct and for double stimuli 5% slower and 13% less correct hits. It was concluded that the developed test was useful in order to detect performance differences between drivers with visual impairments compared to drivers with an unimpaired visual field. However, the test should be completed with other performance assessment of more naturalistic critical traffic situations in order to be used as an instrument to measure “Fitness to drive”. Furthermore, the analysis needs to be complemented with an analysis which consider diagnosis and cognitive status. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.33